MENGINTEGRASIKAN NILAI-NILAI ANTI KORUPSI DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI SEKOLAH MENENGAH ATAS - Nadri Taja; Helmi Aziz (Department of Islamic Education, The State Islamic University Sunan Kalijaga Yogyakarta, 2016)
This paper discusses the anti-corruption values which are supposed to provide a solution to the problems of crime of corruption that are befalling the nation. The research aimed to describe and integrate anticorruption values into subjects of Islamic Education in High School. This is done because the subjects of Islamic Education in High School has a strategic role in achieving the goals of national education which is then internalized into the psyche of learners. The approach used is qualitatively using literature study. From the results of this study found a draft of lesson plan, contained in them values such as honesty, caring, self-reliance, discipline, responsibilities, hard work, temperance, courage and justice.